Ovarian Reserve in Women With Neuromyelitis Optica Spectrum Disorder - Thöne, Jan; Lichtenberg, Solveig; Stahl, Anna; Pache, Florence; Kleiter, Ingo; Ruprecht, Klemens; Gold, Ralf; Hellwig, Kerstin (Frontiers in Neurology, 2018)
Neuromyelitis optica spectrum disorder (NMOSD) is a neuroinflammatory disease. The majority of NMOSD patients is seropositive for aquaporin-4 (AQP4) antibodies. AQP4 is the main water channel protein in the central nervous system, but has also been identified in the female reproductive system. Fertility issues and ovarian reserve has not yet been studied in females with NMOSD. The purpose of this study was to measure serum Anti-Müllerian hormone (AMH) in females with NMOSD compared to healthy controls (HC), in combination with other lifestyle and reproduction parameters. AMH is independent from the menstrual cycle and a reliable indicator of both ovarian reserve and ovarian function. We included a total of 32 reproductive-age females, 18 HC and 14 with NMOSD. We used an enzymatically amplified two-site immunoassay to determine serum AMH level. In comparison to HC, mean AMH value was reduced in NMOSD. Apart from that significantly more women with NMOSD showed low AMH levels (<0.8 ng/ml). Low AMH was associated with disease activity. In contrast, none of the immunotherapies for NMOSD, neither any reproductive life style parameter was associated with a decreased AMH. Our results contribute to understanding of hindered fertility in females with NMOSD and enables neurologists to better counsel female patients.